Public Private People Partnership as Tourism Development Strategy for Kepulauan Bawean - Hikmah, Dzakiyah Adalatul; Maulana, Andika; Kriswibowo, Arimurti (Jurnal Governansi, 2020)
Indonesia has great potentials in the field of tourism. The cumulative data of the Central Statistics Agency in January-August 2019 indicated that the number of foreign tourist visits to Indonesia reached 10.87 million visits or up 2.67 percent compared with the number of foreign tourists visiting the same period in 2018, which amounted to 10.58 million visits. These data indicate that the number of tourists continues to increase and will impact on foreign exchange income both central and regional. However, in reality, tourism potentials in the regional scope lack the spotlight for the central government, and the local government has not been able to manage it. Kepulauan Bawean saves a lot of variety of maritime tourism charm and has an amazing underwater ecological wealth in the form of a group of islands, each of which has its uniqueness. Kepulauan Bawean lies 80 miles from the mainland of Gresik Regency. The purpose of this research is to recommend a strategy for developing tourism model through public-private-people partnerships (4Ps) for Kepulauan Bawean, Gresik Regency. The method used in this research is qualitative descriptive with data collection techniques through interviews and literature review. The results of this research provide a conceptual description of 4Ps and 4Ps implementation steps for Kepulauan Bawean by using the analysis of the application of three-flow theory in the agenda setting consisting of problem stream, policy stream, and political stream. The concept of public-private-people partnership is very suitable to be applied because it involves government, private and community actors to be partner as a tourism development strategy for Kepulauan Bawean. Key words: Kepulauan Bawean, Public-Private-People Partnership, Tourism, Public Service.